Gross Motor Skill Children with Mild Mental Retardation - M Haris Satria; Khoirul Andrianto (Universitas Negeri Medan, 2020)
This study aims to determine the level of gross motor skills of children with mild mental retardation in SD SLB C Karya Ibu Palembang. The type of research in this thesis is qualitative research with quantitative descriptive research methods. The sample in this study were mild mental retardation children from grade I to VI at SD SLB C Karya Ibu Palembang. Instrument test used Test of Gross Motor Development (TGMD) consists of 12 test items, namely run, gallop, hop, leap, horizontal jump, slide, striking stationary ball, stationary dribble, catch, kick, overhand throw and underhand roll The results of measuring the motor skills of students at SD SLB C Karya Ibu Palembang, namely